PERSEPSI MAHASISWA TERHADAP BLENDED E-LEARNING - Maha Lastasa Buju Basafpipana Habaridota (Universitas Tanjungpura, 2023)
AbstractThis study aims to determine student perceptions of blended e-learning with the Google meeting application and WhatsApp group on PPKn Development course for SD/MI PGMI FTIK IAIN Pontianak.This research uses quantitative survey research. The population of this research are students in semester 3 of the academic year 2021/2022 with 150 people. The sample using random sampling technique amounted to 120 people. The type of instrument used is a student perception questionnaire. Perceptions of post-pandemic blended e-learning with an average quality performance index (IKM) of 3.2 in the good category. However, there are two aspects, namely the ease of network access and also the influence on lecture interactions, therefore it is necessary to pay attention for institutions to minimize network disturbances that occurred during online lectures.Keywords: Perceptions, Blended e-learning. AbstrakPenelitian ini bertujuan untuk mengetahui persepsi mahasiswa terhadap pembelajaran blended e-learning dengan aplikasi google meeting dan whatshapp grup pada mata kuliah Pengembangan PPKn SD/MI Prodi PGMI FTIK IAIN Pontianak. Pendekatan penelitian ini menggunakan kuantitatif dengan jenis penelitian survey. Populasi penelitian adalah mahasiswa semester 3 tahun ajaran 2021/2022 berjumlah 150 orang. Sampel menggunakan Teknik random sampling berjumlah 120 orang. Jenis instrument yang digunakan adalah angket persepsi mahasiswa. Persepsi pembelajaran blended e-learning pasca pandemi dengan rata-rata nilai indeks kinerja mutu (IKM) 3,2 dengan kategori baik. Namun ada dua aspek yaitu pada kemudahan akses jaringan dan juga berpengaruh terhadap interaksi perkuliah, maka dari itu perlu menjadi parhatian lembaga untuk menimalisir gangguan-gangguan jaringan yang terjadi saat perkuliahan daring. Kata Kunci: Persepsi, Blended e-learning.